Convergence and Divergence in Private International Law - Liber Amicorum Kurt Siehr - Boele-Woelki, Katharina (EBL-Schweitzer, 2010)
This Liber Amicorum is dedicated to Prof. Dr. Dr. h.c. Kurt Siehr on the occasion of his 75th birthday. The collection honors and celebrates Professor Siehr's academic accomplishments, his writings, and his teachings - a source of continuous inspiration to all those who engage in private international law (conflict of laws) and cultural property law. The contributors - prominent colleagues and friends from around the globe - address law-making aspects of private international law, international family law and succession, international litigation and arbitration, and international cultural prop